2021
DOI: 10.3389/fncel.2021.717209
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Nerve Regeneration, Angiogenesis, and the Immune Response Immediately After Sciatic Nerve Crush Injury in Sprague-Dawley Rats

Abstract: To preliminarily explore the primary changes in the expression of genes involved in peripheral nerve processes, namely, regeneration, angiogenesis, and the immune response, and to identify important molecular therapeutic targets, 45 Sprague-Dawley (SD) rats were randomly divided into a control group and an injury group. In the injury group, tissue samples were collected at 4 and 7 days after the injury for next-generation sequencing (NGS) analysis combined with gene ontology (GO) analysis, Kyoto Encyclopedia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Here, using gene-network theory, we prioritized Sema4a as one of the most prominently upregulated genes in a myelin-enriched gene module strongly affected by BLA–ACC activation. Previous reports had shown that increased Sema4a function contributes to the broad loss of mature oligodendrocytes and demyelination observed in neurological and autoimmune disorders, such as multiple sclerosis 55 58 , 78 . Our results extend these findings in the context of mood regulation, and involve a milder and possibly more localized dysregulation of Sema4a within the ACC.…”
Section: Discussionmentioning
confidence: 96%
“…Here, using gene-network theory, we prioritized Sema4a as one of the most prominently upregulated genes in a myelin-enriched gene module strongly affected by BLA–ACC activation. Previous reports had shown that increased Sema4a function contributes to the broad loss of mature oligodendrocytes and demyelination observed in neurological and autoimmune disorders, such as multiple sclerosis 55 58 , 78 . Our results extend these findings in the context of mood regulation, and involve a milder and possibly more localized dysregulation of Sema4a within the ACC.…”
Section: Discussionmentioning
confidence: 96%
“…Here, using gene network theory, we prioritized Sema4a as one of the most prominently upregulated genes in a myelin-enriched gene module strongly affected by BLA-ACC activation. Previous reports have shown that increased Sema4a function contributes to the broad and profound loss of mature oligodendrocytes and demyelination observed in neurological and autoimmune disorders, such as multiple sclerosis [52][53][54][55]72 . Our results extend these findings to a milder and more localized dysregulation of Sema4a signaling in the ACC, in the context of mood regulation.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, CCR5 has been correlated with obesity, adipose tissue inflammation, and insulin resistance in both animal and human studies [ 18 , 19 ], and acute exercise may upregulate CCR5 expression in the skeletal muscles of patients with PCOS [ 20 ]. A recent study also revealed that CCR5 is associated with the regeneration, angiogenesis, and immune response of nerves from four to seven days after injury [ 21 ]. Further, the autosomal recessive deficiencies of CCR5 underlie resistance to HIV-1 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%